Pendampingan Integrasi Ecoprint Steam Based dalam Projek Penguatan Profil Pelajar Pancasila pada Kurikulum Merdeka Sebagai Inovasi Creative Educational Media di SDN Sahang - Indah Listia Rahayu; Jauhan Budiwan (Social Science Academic, 2025)
This study aims to demonstrate that the integration of STEAM-based ecoprint into the Strengthening the Profile of Pancasila Students (P5) project within the Merdeka Curriculum can serve as an innovative and relevant learning approach at SDN Sahang. Ecoprint, an environmentally friendly technique that utilizes local plants and natural resources, is combined with the STEAM framework (Science, Technology, Engineering, Arts, and Mathematics) to develop creative, contextual, and meaningful educational media. The research employs the ABCD (Asset-Based Community Development) method, which emphasizes the identification and empowerment of existing assets within the school and local community to support sustainable and collaborative learning. The findings reveal that the implementation of STEAM-based ecoprint not only enhances students’ creativity, critical thinking, and environmental awareness but also strengthens character values aligned with the Pancasila student profile. Furthermore, this innovation fosters interdisciplinary learning and provides a practical example of how local culture and knowledge can be integrated into modern educational practices, in accordance with the goals of the Merdeka Curriculum